(untitled) (Human-Computer Interaction Perspectives, 2022)
This paper investigates the pivotal role of Artificial Intelligence (AI) and Machine Learning (ML) in revolutionizing workers’ compensation risk management practices. Employing advanced AI and ML technologies has enabled the development of sophisticated tools for predicting workplace injuries, facilitating efficient return-to-work programs, and enhancing fraud detection mechanisms. By leveraging large datasets and complex algorithms, these technologies offer invaluable insights into risk assessment and mitigation strategies, ultimately leading to improved safety outcomes and cost savings for employers. This research explores the various applications of AI and ML in workers’ compensation risk management and highlights their potential to transform traditional approaches in ensuring occupational health and safety.